PEMBELAJARAN MEMBACA PERMULAAN MELALUI PERMAINAN BAHASA SISWA KELAS I SDN BULAKREJO MADIUN - Samsiyah, Nur; Sari, Apri Kartika; Sulistyaningrum, Yuni (Premiere Educandum, 2013)
Early reading is a stage of learning reading for elementary school students of early grades. They learn to acquire the reading skill and techniques  tosuccessfully  decode  passages.  Learning  atmosphere should be created through the language plays for reading. It goes with their characteristic of enjoying playing, Language playsplay a vital role to support their cognitive and social development. The current study aims to describe the process as well as the results of  early reading  through  a  language  play  at  early  grades  of  elementary school.   Qualitatively   approached,   the   current   study   involves participants  of  the  first  graders  of  the  elementary  school  SDN Bulakrejo Madiun.  Data  were  collected  through  observation  and documentation. Results show: (1) high achievement of average 80.7; (2) high enthusiasm specifically on the play batuloncatan (stepping stone); (3) the play could be carried out in and out of classroom and increasing their interest; and (4) headmaster, teachers and students appreciate the learning reading through the play. Key words : Early Reading, Play